2022
DOI: 10.1111/jpi.12810
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin mediates reactive oxygen species homeostasis via SlCV to regulate leaf senescence in tomato plants

Abstract: Melatonin (MT) functions in removing reactive oxygen species (ROS) and delaying plant senescence, thereby acting as an antioxidant; however, the molecular mechanism underlying the specific action of MT is unclear. Herein, we used the mutant plants carrying the MT decomposition gene melatonin 3‐hydroxylase (M3H) in tomato to elucidate the specific mechanism of action of MT. SlM3H‐OE accelerated senescence by decreasing the content of endogenous MT in plants. SlM3H is a senescence‐related gene that positively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…(2018) confirmed that melatonin synthesis enzymes ( MeTDC2 and MeASMT2/3 ) interact with MeWRKY20/75 to form a protein complex that extends the complex signaling of melatonin modulation. Not only ROS reduction in PSII but also circadian rhythm fluctuations have been mediated in melatonin-treated tomato, according to the weakened interaction between Sl CV and Sl PsbO /Sl CAT3 /Sl M3H ( Yu et al., 2022 ). In addition, a set of miRNAs (such as miR8029-3p, miR159-5p, miR858, and novel-m0048-3p) is able to negatively regulate target mRNAs in response to melatonin-mediated cold resistance ( Li et al., 2016 ).…”
Section: Melatonin Functions Against Abiotic Stressmentioning
confidence: 99%
“…(2018) confirmed that melatonin synthesis enzymes ( MeTDC2 and MeASMT2/3 ) interact with MeWRKY20/75 to form a protein complex that extends the complex signaling of melatonin modulation. Not only ROS reduction in PSII but also circadian rhythm fluctuations have been mediated in melatonin-treated tomato, according to the weakened interaction between Sl CV and Sl PsbO /Sl CAT3 /Sl M3H ( Yu et al., 2022 ). In addition, a set of miRNAs (such as miR8029-3p, miR159-5p, miR858, and novel-m0048-3p) is able to negatively regulate target mRNAs in response to melatonin-mediated cold resistance ( Li et al., 2016 ).…”
Section: Melatonin Functions Against Abiotic Stressmentioning
confidence: 99%
“…305 M3H overexpression in transgenic rice increased the number of secondary tiller and panicles that are pivotal agronomic traits governing grain yield, while the accelerated leaf senescence was observed in M3H overexpressing tomato. 309,310 Arabidopsis M3H knockout mutant exhibited retarded growth with rosette leaves and delayed flowering. 306 Phylogenetic analysis is important for evaluating functional conservation and diversification of gene family (Figure 8B).…”
Section: Functional Diversity Of Melatonin Metabolic Genesmentioning
confidence: 99%
“…307 M3H from Solanaceae were clustered into clades A and B implying functional differentiation in plant reproductive growth. 310 The close relationship of M3H from cotton, grape, and soybean with that from Arabidopsis suggested their conservation function in seedling growth and flowering. 306 M3H in cereal plant had an important role in grain yield.…”
Section: Functional Diversity Of Melatonin Metabolic Genesmentioning
confidence: 99%
See 2 more Smart Citations